2021
DOI: 10.1371/journal.pone.0252562
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of regulatory behavior in the still-face paradigm at 3 months: A comparison of Brazilian and Portuguese infants

Abstract: Three infant regulatory behavior patterns have been identified during the Face-to-Face Still-Face paradigm (FFSF) in prior research samples: a Social-Positive Oriented pattern (i.e., infants exhibit predominantly positive social engagement), a Distressed-Inconsolable pattern (i.e., infants display conspicuous negative affect that persists or increases across FFSF episodes), and a Self-Comfort Oriented pattern (e.g., infants primarily engage in self-comforting behaviors such as thumb-sucking). However, few stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
2
0
0
Order By: Relevance
“…However, it is hard to attribute the difference in the results across different studies solely to differences in infants' prematurity status (FT, MLPT, or VEPT), because many of the families in the current sample also were from higher social risk backgrounds. Another study carried out with a low-income Brazilian sample of infants born FT (Fuertes et al, 2021) found a similar prevalence of the three infant regulatory patterns as in the current study. It may be that the cumulative family and social risk factors experienced by some families in the current sample may have indirectly jeopardized parents' ability to support their infants in regulating their emotions during stressful situations, by increasing their allostatic load Diener et al, 2003;Moster et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, it is hard to attribute the difference in the results across different studies solely to differences in infants' prematurity status (FT, MLPT, or VEPT), because many of the families in the current sample also were from higher social risk backgrounds. Another study carried out with a low-income Brazilian sample of infants born FT (Fuertes et al, 2021) found a similar prevalence of the three infant regulatory patterns as in the current study. It may be that the cumulative family and social risk factors experienced by some families in the current sample may have indirectly jeopardized parents' ability to support their infants in regulating their emotions during stressful situations, by increasing their allostatic load Diener et al, 2003;Moster et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…In the current sample of infants born VEPT, we were able to identify the same three patterns of infant regulatory behavior as were observed in prior studies with infants born FT or MLPT (Fuertes et al., 2021), despite these infants’ greater biological and neurological immaturity and vulnerability. However, the prevalence of each pattern in the current sample varies from that observed in prior work.…”
Section: Discussionsupporting
confidence: 77%